Синтагматика и парадигматика в фонологических решениях - Воронкова, Г. В. (Kalbotyra, 1981)
The author of the paper maintains that the contradictoriness of certain phoneme conceptions, for instance, the conceptions of phoneme as a sound element, is due to the fact that the originators of those conceptions take no account of the connection existing between paradigmatics and syntagmatics.